Improving EU Market Access for Jordanian Exports - Stéphanie Brunelin; Jaime de Melo; Alberto Portugal-Perez (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
A request for relaxing current Rules of Origin (RoO) under the EU-Jordan FTA have been proposed under a EU/friends of Jordan initiative. This brève reviews RoO requirements under the EU-Jordan FTA and compares them with those under the Jordan-US FTA. It also compares the utilization of preferences under both FTAs that have been in existence for over a decade and fully operative for over five years. Preferential access, while higher for the US, is still substantial for the EU. In 2012, the most recent year for which preference utilization rates can be calculated, preference utilization is systematically higher under the US-Jordan FTA. In the high-preference, labour-intensive apparel sector (with 15%-18% preferential margin for sales in the US market and 11%-12% for sales in the EU markets), utilization of preferences for Jordanian sales in the US market are 99.5%, whereas utilization for sales in the EU market is only 50% (table A2). Similar patterns hold for other sectors and in the case of the EU-Jordan FTA, utilization of preferences in the top 10 sectors with the highest preference margins is low while it is 100% for the corresponding sectors in the Jordan-US FTA (table A5).Three pathways are suggested for simplification of RoO: (i) relaxing the double-transformation rule in apparel (yarn can be sourced from non-members but textiles must be sourced among PanEuroMed members) to a single-transformation-rule allowing for non-originating textiles should contribute to make Jordan attractive for Foreign Direct Investment in apparel to service the EU market; (ii) eliminating RoO requirements for tariff lines with unadjusted preferential margins below 3% —which corresponds to the middle range of estimates of fixed costs, at least for small firms—would also help Jordanian exporters who typically export small volumes to the EU; (iii) implementing a low uniform across-the-board value content rule perhaps combined with a Change of Tariff Classification (CTC) at the subheading (HS6) or heading (HS4) level. Note: Since this work was completed in March, the EU announced a relaxation of RoO for a twenty-year period allowing for up to 70 percent non-originating material manufactured in SEZs for origin that are manufactured in designated development zones and industrial estates in Jordan including 50 harmonised system non-agricultural chapters. See http://www.jordantimes.com/news/local/jordan-eu-relaxed%E2%80%99-rules-origin-deal-goes-effect-10-years
Keywords: 330